2021
DOI: 10.1111/anu.13410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of host‐associated probioticBacillus altitudinisB61‐34b on growth performance, immune response and disease resistance of Nile tilapia (Oreochromis niloticus) raised under biofloc system

Abstract: This investigation was performed to assess the influences of the host-associated probiotic Bacillus altitudinis B61-34b (BAA) on growth, immune response and disease resistance to Streptococcus agalactiae in Nile tilapia (Oreochromis niloticus). Fish (25.50 ± 0.52 g fish −1 ) were distributed into 15 aquaria (150 litres tank −1 ) at density of 20 fish tank −1 . The fish were fed basal diets with BAA inclusions in different concentrations: 0 (BAA1-Control), 10 6 (BAA2), 10 7 (BAA3), 10 8 (BAA4) and 10 9 (BAA5) C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…The findings of the present research displayed that growth indices were improved in all groups, particularly in the Diet 2 group. Similarly to our findings, several studies reported that the use of different probiotics has positive effects on growth performances in different aquatic species (Abdel-Aziz et al, 2020;Lee et al, 2021;Sayed Hassani et al, 2020;Sutriana et al, 2021;Tarkhani et al, 2020;Van Doan, Lumsangkul, Jaturasitha, et al, 2021;Van Doan, Lumsangkul, Ruangwong, et al, 2021;Zhang et al, 2022). Probiotics by increasing the ability to absorb minerals such as calcium, improving the intestinal microbial balance (Aljewicz et al, 2014;El-Saadony et al, 2021;Hoseinifar et al, 2020;Nath et al, 2019;Van Doan et al, 2019), production of digestive enzymes, improving food efficiency, reduction of anti-nutritional factors (Assan et al, 2022) and production of short- According to our findings, fish fed with all probiotic groups for 60 days had higher amounts of intestinal ɑ-amylase, protease and lipase.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present research displayed that growth indices were improved in all groups, particularly in the Diet 2 group. Similarly to our findings, several studies reported that the use of different probiotics has positive effects on growth performances in different aquatic species (Abdel-Aziz et al, 2020;Lee et al, 2021;Sayed Hassani et al, 2020;Sutriana et al, 2021;Tarkhani et al, 2020;Van Doan, Lumsangkul, Jaturasitha, et al, 2021;Van Doan, Lumsangkul, Ruangwong, et al, 2021;Zhang et al, 2022). Probiotics by increasing the ability to absorb minerals such as calcium, improving the intestinal microbial balance (Aljewicz et al, 2014;El-Saadony et al, 2021;Hoseinifar et al, 2020;Nath et al, 2019;Van Doan et al, 2019), production of digestive enzymes, improving food efficiency, reduction of anti-nutritional factors (Assan et al, 2022) and production of short- According to our findings, fish fed with all probiotic groups for 60 days had higher amounts of intestinal ɑ-amylase, protease and lipase.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that the use of probiotics in biofloc systems can enhance the production and health of aquatic animals [ 73 , 74 ]. For example, the use of Bacillus sp.…”
Section: What Goes Right?mentioning
confidence: 99%
“…For example, the use of Bacillus sp. in BFT systems has been shown to improve the growth performance and disease resistance of Nile tilapia [ 74 , 75 ]. Similarly, the use of Lactobacillus plantarum in biofloc systems has been shown to improve the growth performance and survival rate of Pacific white shrimp [ 76 ].…”
Section: What Goes Right?mentioning
confidence: 99%